An Unanticipated Outcome of Undergraduate Research Experiences for Community College Students: Creation of a Materials Science and Engineering Educational Program. Issue 1762 (11th May 2015) - Sheinberg, Bartlett M.
ABSTRACT: Since 2005 the West Houston Center for Science & Engineering (WHC) has provided opportunities for select cohorts of community college students to participate in summer research experiences. Participating research institutions include regional universities, NASA-JSC and Sandia National Laboratories (NM). Research activities cross numerous engineering, physical and biological sciences, and computational disciplines, and have been supported by federal agencies and corporate/educational foundations. These experiences have generated three important outcomes: (1) Providing significant motivation for students regarding university transfer and completion; (2) Generating realistic expectations for students regarding completion of their undergraduate degrees, and transitioning into the science and engineering workforce and/or graduate school; and, (3) Providing support for the creation of a formal materials science educational program at the West Houston Center. This paper describes the influence and impact that the Materials Research Society, through its members, conferences, and working committees, has contributed to the transition of the West Houston Center as it moves from a broad based science and engineering educational center to one with a concentration on materials science.